The influence of capitation grants on quality education delivery in Tanzania public secondary schools during the time of inflation - Leoncia Ndaula; Majiyd H. Suru; Calvin Z. Swai (Heliyon)
This study investigated the influence of capitation grants on quality education delivery in public secondary schools during the time of inflation in Tanzania. The study used a mixed research approach using a concurrent research design. Data were collected from four heads of school and sixty-two teachers through interviews, and questionnaires respectively. The qualitative data were analysed thematically, while quantitative data were analysed descriptively. The findings revealed that the capitation grants influence shortage and delay of teaching and learning materials; poor infrastructure; deprived implementation of extracurricular activities and health services. The study concluded that the allocation of adequate capitation grants for improving teaching and learning environments significantly influenced the management of secondary schools for quality education delivery. The study recommends the reviews of the current capitation grants allocated to secondary schools by the government of Tanzania, to match the current inflationary situation.